Loyalty (the national principles): strengthening eco-tourism industry in Sabah, Malaysia - Romzi Ationg; Ahmad Tarmizi Abdul Rahman; Mansur Tola; Anna Lynn Abu Bakar; Budi Anto Mohd Tamring; Nordin Moen (Canadian Center of Science and Education, 2016)
The purpose of this study was to investigate the youth’s perception on the influences of the second National Principles (Rukun Negara no. 2) that is ‘loyalty to the king and country’ towards the eco-tourism industry in Sabah, Malaysia. This study aims to determine the positive and negative influences of the second National Principles (NP) on the eco-tourism industry; and to determine the factor associated most with the success of eco-tourism industry in relation to the second NP as perceived by youth in Sabah, Malaysia. The data were collected through a self administered questionnaire and later analyzed using SPSS. In this study, 100 youth were selected as respondents with a mean age of 27. This study found that there is a positive influence but no negative influence of the second NP on the eco-tourism industry in Sabah, Malaysia. The factor associated most with the success of eco-tourism industry in relation to the second NP as perceived by youth in Sabah, Malaysia is ethical and moral values. In accordance, professional experience, and the use of a specific formula may provide a suitable basis for change in this industry when dealing with the local perception on their responsibility to make this industry develop in relation to their feeling of concern towards ‘loyalty to the king and country’